PENINGKATAN KETERAMPILAN MENULIS TEKS EKSPOSISI MENGGUNAKAN MODEL BRAIN WRITING PADA PESERTA DIDIK KELAS IV SDN 24 UJUNG GURUN KOTA PADANG - Nogo Karangora, Maria Berliana; Sukma, Elfia; Habibi, M; Meizatri, Ranti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the low exposition text writing skills of fourth-grade students of SDN 24 Ujung Gurun, Padang City, which is characterized by difficulties in developing ideas into written form, understanding the structure of exposition texts, and using standard language appropriately. Students also often rely on personal opinions and lack motivation in learning to write. This study aims to improve exposition text writing skills using the Brain Writing model. This type of research is Classroom Action Research (CAR) with a qualitative and quantitative approach, which is carried out in two cycles including the planning, implementation, observation, and reflection stages. The subjects of this study consisted of one teacher and 29 fourth-grade students. The results of the study showed a significant increase in every aspect. The quality of learning planning (teaching modules) increased from an average of 89.5 in Cycle I with good qualifications to 95.8 in Cycle II with very good qualifications. Teacher and student activities increased from 92.04 in Cycle I with very good qualifications to 97.72 in Cycle II with very good qualifications. This improvement had a positive impact on student learning outcomes, where the average value of expository text writing skills increased from 80.4 with good qualifications in cycle I, to 95.62 with very good qualifications in cycle II. It can be concluded that the Brain Writing Model is effective in improving expository text writing skills in elementary school students.